Aulus Gelliusz, Noce attyckie XVII 10 - w kierunku interpretacji i przekładu - Ochman, Katarzyna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2015)
The article is a translation into Polish of one section of Attic Nights and its interpretation.
Keywords: Aulus Gellius; Noce attyckie; Wergiliusz; Pindar